Fluid evolution and ore genesis of the Dalingshang deposit, Dahutang W-Cu ore field, northern Jiangxi Province, South China - Peng, Ning-Jun; Jiang, Shao-Yong; Xiong, Suo-Fei; Pi, Dao-Hui (Mineralium deposita, 2018)
The Dalingshang W-Cu deposit is located in the North section of the Dahutang ore field, northern Jiangxi Province, South China. Vein- and breccia-style tungsten-copper mineralization is genetically associated with Mesozoic S-type granitic rocks. Infrared and conventional microthermometric studies of both gangue and ore minerals show that the homogenization temperatures for primary fluid inclusions in wolframite (~ 340 °C) are similar to those in scheelite (~ 330 °C), but about 40 °C higher than those of apatite (~ 300 °C) and generally 70 °C higher than those in coexisting quartz (~ 270 °C). Laser Raman analysis identifies CH 4 and N 2 without CO 2 in fluid inclusions in scheelite and coexisting quartz, while fluid inclusions in quartz of the sulfide stage have variable CO 2 content. The ore-forming fluids overall are characterized by high- to medium-temperature, low-salinity, CH 4 , N 2 , and/or CO 2 -bearing aqueous fluids. Chalcopyrite, muscovite, and sphalerite are the most abundant solids recognized in fluid inclusions from different ores. The H-O-S-Pb isotope compositions favor a dominantly magmatic origin for ores and fluids, while some depleted δ 34 S values (− 14.4 to − 0.9‰) of sulfides from the sulfide stage are most likely produced by an increase of oxygen fugacity, possibly caused by inflow of oxidized meteoric waters. The microthermometric data also indicate that a simple cooling process formed early scheelite and wolframite. However, increasing involvement of meteoric waters and fluid mixing may trigger a successive deposition of base metal sulfides. Fluid-rock interaction was critical for scheelite mineralization as indicated by in-situ LA-ICP-MS analysis of trace elements in scheelite.